Postmodern public administration - Fox, Charles; Miller, Hugh (California: Sage Publications, Inc, 1996)
Contents: 1. a new approarch to democratic governance. 2. orthodox y and its alternatives. I. the loop model of democracy. II. quixotic mainstream reforms. III. the institutionalist/constitutionalist alternative. IV. communitarian/citizen alternative. V. the need for discourse theory. 3. the growing gap between words and deeds: postmodern symbolic politics. 4. theoretical underpininmings of discurse theory: phenomenology, constructivism structuration theory, and energy fields. 5. warrants for discourse 6. nascent forms of discourse
Keywords: Public Administration